Relocation of container-based services in a MEC-NFV orchestrated environment - Bernad, Cristina; Kjorveziroski, Vojdan; Roig, Pedro; Alcaraz, Salvador; Gilly, Katja; Filiposka, Sonja (Springer, 2024)
With the rapid growth of real-time next-generation mobile services, it has become necessary to work towards holistic orchestration of the benefits promised with edge computing based on bringing the computing infrastructure closer to the end user. While the concept of Multi-access Edge Computing (MEC) integrated with Network Function Virtualisation (NFV) is being standardised, there is still a lot of work to be done to orchestrate the relocation of edge applications integrated in 5G and beyond systems in a smooth and efficient manner. In this paper, we document the current status of the transparent relocation of edge services in an experimentally deployed MEC-NFV environment based on OSM. Working towards gathering monitoring training datasets necessary for the development of proactive MEC application orchestrators that will implement seamless follow-me behaviour for MEC services, we provide benchmark results for the service downtime of three potential MEC services hosted in lightweight containers. Our analysis of results shows that containers exhibit improved performance over that of virtual machines, but there are still some issues that require improvement in both the orchestration implementation as well at the relocation process for containers.
The final publication is available at Springer via http://dx.doi.org/10.1007/978-3-031-81900-1_1
Keywords: Edge Computing; Optimisation; Standardisation; Migration; Mobile Nodes; Containers